Analysis of the Reliability of Template Storage When Implementing Modern Biometric Technologies in Information Security Systems - Safiullina, L. Kh; Kasimova, A. R.; Alekseeva, A. A. (Automatic control and computer sciences, 2024)
It can be argued that in certain areas of information technology, classical systems of authentication of the user of a computer system based on passwords and tokens are being completely replaced by biometric technologies. However, biometric systems are vulnerable to various types of security threats. For example, unlike the same passwords and tokens, biometric-based templates cannot be replaced in the event of a compromise. To solve this problem, new protection schemes have been developed. They can be conditionally divided into two groups: biometric cryptography and cancelable biometrics. Biometric cryptography methods show average values of errors of the first and second kind and experimental work in this area is widely known. Cancellable biometrics can be highly reliable, but there are limited experimental data on them. A comparative analysis of the reliability of existing methods is presented. It has been shown that among static biometric parameters, the iris is of greatest interest, and among dynamic ones, keyboard handwriting is of greatest interest. However, the use of these methods, like others, has its own difficulties and risks.